1998
DOI: 10.1159/000028266
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endogenous Nitric Oxide Synthesis Potentiates the Effects of Sodium Nitroprusside but Not of Adenosine in Experimental Pulmonary Hypertension

Abstract: This study examined the systemic and pulmonary vasodilator effects of sodium nitroprusside (SNP) and adenosine during experimental pulmonary hypertension with and without inhibition of endogenous NO synthesis. Male New Zealand White rabbits were anesthetized and mechanically ventilated. The NO synthesis inhibitor NG-nitro-L-arginine methyl ester (L-NAME) was administered to 15 of the 28 rabbits. Pulmonary hypertension was then produced in all rabbits by U46619, a thromboxane A2 mimetic. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It is not due to a general toxic eVect on, for example, circulation or respiration as rabbits tolerate several hours of the employed L-NAME dose with periods of marked hypoxic challenge (Persson et al 1990). It has been shown in rabbits that NOS inhibition slightly increases basal pulmonary vascular resistance (Persson et al 1990) and severely augments the pulmonary hypertension induced by hypoxia (Persson et al 1990) and a thromboxane A 2 -mimetic (Wall et al 1999). A contributing factor to the reduced survival rate in the present study and in that of WisloV et al (2003) could thus be that NOS inhibition resulted in a pulmonary hypertension that worsened the impact of VGE in the lung circulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is not due to a general toxic eVect on, for example, circulation or respiration as rabbits tolerate several hours of the employed L-NAME dose with periods of marked hypoxic challenge (Persson et al 1990). It has been shown in rabbits that NOS inhibition slightly increases basal pulmonary vascular resistance (Persson et al 1990) and severely augments the pulmonary hypertension induced by hypoxia (Persson et al 1990) and a thromboxane A 2 -mimetic (Wall et al 1999). A contributing factor to the reduced survival rate in the present study and in that of WisloV et al (2003) could thus be that NOS inhibition resulted in a pulmonary hypertension that worsened the impact of VGE in the lung circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that endogenous NO synthesis inhibition does not affect basal pulmonary arterial pressure in dogs ( Sander et al ., 2003 ) and moderately increases basal pulmonary vascular resistance in rabbits ( Persson et al ., 1990 ), and severely augments hypoxic vasoconstriction in rabbits ( Persson et al ., 1990 ) and dogs ( Sander et al ., 2003 ). Another example of a condition where inhibited NO synthesis enhances pulmonary hypertension is during thromboxane A 2 mimetic‐induced pulmonary hypertension in rabbits ( Wall et al ., 1999 ). It is also known that endogenous NO is a regulator of heart performance ( Paulus and Bronzwaer, 2004 ) and that acute NO synthase inhibition reduces myocardial oxygen consumption and myocardial contractility ( Sherman et al ., 1997 ).…”
Section: Discussionmentioning
confidence: 99%